(untitled) (Seven Editora, 2023)
The main objective of this paper is to examine the relationship between the Circular Economy (CI) and Corporate Social Responsibility (CSR) in Brazil. The work is structured as follows: in a first point the objective, the working hypothesis and the methodology used are defined and problematized; second, both concepts are defined and problematized, including the state of the art on CD and CSR, and are linked to each other, establishing the particularities of each of them; thirdly, in the central part of the work, the advances achieved in QE and CSR in Brazilian society and economy are exposed and subjected to criticism, in addition to examining how the two variables are linked; Finally, the results reached in the research are presented and discussed, and both the limitations of the work and possible lines of research are exposed. DOI: 10.56238/pacfdnsv1-007